ARTIS DANGDUT NASIONAL SEBAGAI MEDIA KAMPANYE BUPATI TERPILIH TAHUN 2015 DI SOPPENG - Mrs Novita (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2019)
Based on the results of the study show that, (1) the popularity of national dangdut artists in Soppeng District began in the 2000s to the present, when the emergence of talent search events on television stations in 2004 and in 2014 began to show singers from South Sulawesi, namely Aty Selayar (2014), Evi Masamba (2015) and Selfi Soppeng (2018) at the time of the appearance of singers from the province of South Sulawesi, making people increasingly like watching dangdut in Soppeng Regency; (2) Consideration of the selection of national dangdut artists as a campaign media, dangdut is considered to have many fans, the needs of people who like dangdut, the existence of television programs that show dangdut talent shows, dangdut who are populist and dangdut close to the people, and dangdut is considered move the masses; (3) The effectiveness of the selection of national dangdut artists as campaign media was not the main factor of the majority of votes, the most votes were door to door, dangdut was only used by the success team, the regents and deputy district heads were chosen as mass media to go to the campaign locations so that the candidates looks a lot when holding a grand campaign